Skin and subcutaneous fascia closure at caesarean section to reduce wound complications: the closure randomised trial - Amanda J. Poprzeczny; Rosalie M. Grivell; Jennie Louise; Andrea R. Deussen; Jodie M. Dodd (BMC, 2020)
Abstract Background Wound infection is a common complication following caesarean section. Factors influencing the risk of infection may include the suture material for skin closure, and closure of the subcutaneous fascia. We assessed the effect of skin closure with absorbable versus non-absorbable suture, and closure versus non-closure of the subcutaneous fascia on risk of wound infection following Caesarean section. Methods Women undergoing caesarean birth at an Adelaide maternity hospital were eligible for recruitment to a randomised trial using a 2 × 2 factorial design. Women were randomised to either closure or non-closure of the subcutaneous fascia and to subcuticular skin closure with an absorbable or non-absorbable suture. Participants were randomised to each of the two interventions into one of 4 possible groups: Group 1 - non-absorbable skin suture and non-closure of the subcutaneous fascia; Group 2 - absorbable skin suture and non-closure of the subcutaneous fascia; Group 3 - non-absorbable skin suture and closure of the subcutaneous fascia; and Group 4 - absorbable skin suture and closure of the subcutaneous fascia. The primary outcomes were reported wound infection and wound haematoma or seroma within the first 30 days after birth. Results A total of 851 women were recruited and randomised, with 849 women included in the analyses (Group 1: 216 women; Group 2: 212 women; Group 3: 212 women; Group 4: 211 women). In women who underwent fascia closure, there was a statistically significant increase in risk of wound infection within 30 days post-operatively for those who had skin closure with an absorbable suture (Group 4), compared with women who had skin closure with a non-absorbable suture (Group 3) (adjusted RR 2.17; 95% CI 1.05, 4.45; p = 0.035). There was no significant difference in risk of wound infection for absorbable vs non-absorbable sutures in women who did not undergo fascia closure. Conclusion The combination of subcutaneous fascia closure and skin closure with an absorbable suture may be associated with an increased risk of reported wound infection after caesarean section. Trial registration Prospectively registered with the Australian and New Zealand Clinical Trials Registry, number ACTRN12608000143325 , on the 20th March, 2008.